THE CHALLENGES IN THE TEACHING OF ENGLISH LITERATURE: A SYSTEMATIC REVIEW - Nur Syafiqa Mohd Nawi; Nurul Asma’ Amani Muhmad Nor Nor (UIBU, 2023)
Learning English is already a challenging task, and when it comes to studying literature in English, the difficulty level increases even further. This Systematic Literature Review (SLR) is conducted to identify important challenges in the teaching and learning of English literature. The whole process of conducting this SLR followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. PRISMA is a graphical representation of the complete process of doing a systematic review and meta-analysis, including the search for relevant articles, the filtering of them based on certain criteria, and the assessment of their quality. The results show that the factors can be categorized into three: student-related challenges, teacher-related challenges, and external-related challenges. This paper reports the key gap and limitations in current study that focuses on the challenges in the teaching and learning of English literature.